A woman is a woman, A married woman, Two or three things I know about her three films - Godard, Jean-Luc 1930-2022 (Classic film scripts)
The three films, A Woman is a Woman (1961), A Married Woman (1964), and Two or Three Things That I know About Her (1966), form a trilogy which the director, at different stages of his career, deals with twenty four hours in the life of a woman living in Paris. The book illustrates Godard's ability to break away from cinematic conventions. As a director of the new wave, he is continually experimenting with language and technique; and throughout these controversial features his social awareness and political commitment are brilliantly illustrated.